The Theoretical Issue of Social Security—International and European Perspectives - Jakab, Nóra; Solymosi-Szekeres, Bernadett (Sustainability Of The Social Security System: Demographic Challenges and Answers in Central Europe, 2023)
This chapter deals with the theoretical issue of social security. It has been presented by the main characteristics of social rights, the international social law and main features of the EU legislation in this regard. These provide a broad understanding of the issue at international and European level. It was highlighted that human rights are indivisible, interdependent and interrelated rights. The quality of human existence is determined by second generation rights. Social security is an integral part of a life worth living. There is a difference between the nature of each generation, one thing can be said with certainty: all human beings havean indivisible right to human rights, and the quality of human life is largely determined by the opportunities offered by these social rights, and the presence of the state is present in all generational rights, differing only in the extent and intensity of their presence. KEYWORDS: international social law, social rights, sources of international social law, EU legislation